2018
DOI: 10.1007/978-3-319-68369-0
|View full text |Cite
|
Sign up to set email alerts
|

Practical Decision Making using Super Decisions v3

Abstract: SpringerBriefs present concise summaries of cutting-edge research and practical applications across a wide spectrum of fields. Featuring compact volumes of 50 to 125 pages, the series covers a range of content from professional to academic. Typical topics might include:• A timely report of state-of-the art analytical techniques • A bridge between new research results, as published in journal articles, and a contextual literature review • A snapshot of a hot or emerging topic • An in-depth case study or clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 0 publications
0
42
0
Order By: Relevance
“…PCM results were calculated according to the well-known procedure described in [44][45][46], and specifically to [47] (pp. 12-15) for the consistency ratio calculation.…”
Section: Methodology For Results Assessmentmentioning
confidence: 99%
“…PCM results were calculated according to the well-known procedure described in [44][45][46], and specifically to [47] (pp. 12-15) for the consistency ratio calculation.…”
Section: Methodology For Results Assessmentmentioning
confidence: 99%
“…Super Decisions software v. 3.2 [56] is used to solve the decision-making problem based on AHP. The steps of a typical AHP procedure are ranged as follows [57];…”
Section: Formulation Of the Proposed Criteria Using Ahpmentioning
confidence: 99%
“…Super Decisions software v.3.2 [56] is used to solve the decision-making problem based on AHP. The steps of a typical AHP procedure are ranged as follows; [57] 1. Developing a hierarchical model: The hierarchy consists of clusters arranged in levels to analyze the decision.…”
Section: Formulation Of the Proposed Criteria Using Ahpmentioning
confidence: 99%
See 1 more Smart Citation
“…Important criteria for policy options derived from the initial literature review are suggested to be health impact, cost of implementation, and feasibility (36). Finally, these options will be ranked using the analytic hierarchy process (AHP) technique (37) to provide the most appropriate policy options in the current situation for Tabriz metropolis, possibly implementable in other cities with similar characteristics.…”
Section: Fourth Phase: Analysis and Prioritizing The Policy Optionsmentioning
confidence: 99%